1989
DOI: 10.1111/j.1533-8525.1989.tb01527.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Job Satisfaction: Why Aren't Women More Dissatisfied?

Abstract: This article analyzes gender differences in job satisfaction among full-time workers. Why do women report equal or greater job satisfaction than men in spite of objectively inferior jobs? Analysis reveals few differences between men and women in the determinants of job satisfaction when considering job characteristics, family responsibilities, and personal expectations. Little support is found for theories that men and women: (1) focus on different aspects of work in axriving at a given level of job satisfacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
144
3
12

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(169 citation statements)
references
References 22 publications
10
144
3
12
Order By: Relevance
“…Finally, level of job satisfaction was the same for both genders, which is in accordance with numerous previous research (Brief, Rose, & Aldag, 1977;De Vaus & McAllister, 1991;Mottazl, 1986;Smith, & Hoy, 1998;Tait, Padgett, & Baldwin, 1989;Ugorji, 1997;Witt & Nye, 1992). This also indicates our assumptions were erroneous, because we expected women to be more satisfied than men, like many authors proved previously (Clark, 1996(Clark, , 1997Hodson, 1989;Murray & Atkinson, 1981;Sloane & Williams, 1996).…”
Section: Research Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Finally, level of job satisfaction was the same for both genders, which is in accordance with numerous previous research (Brief, Rose, & Aldag, 1977;De Vaus & McAllister, 1991;Mottazl, 1986;Smith, & Hoy, 1998;Tait, Padgett, & Baldwin, 1989;Ugorji, 1997;Witt & Nye, 1992). This also indicates our assumptions were erroneous, because we expected women to be more satisfied than men, like many authors proved previously (Clark, 1996(Clark, , 1997Hodson, 1989;Murray & Atkinson, 1981;Sloane & Williams, 1996).…”
Section: Research Resultssupporting
confidence: 72%
“…men would value and perceive more organisational support and precise work procedure, than women. we assume that women will show higher level of job satisfaction than men, like in the studies mentioned earlier (Clark, 1996;Hodson, 1989;Murray & Atkinson, 1981;Sloane & Williams, 1996).…”
Section: The Present Studymentioning
confidence: 99%
“…Studying the factor that affect job satisfaction the literature of current study referred to those factors that are very close to teacher turnover in universities that shows that dissatisfied teachers more likely to switch from there institutions (Hodson, 1989). This is also studied from previous research in other disciplined like management, Marketing and in organizational behavior shown that HR practices are primary indicator of job satisfaction to the work (Mottaz, 1985).…”
Section: Job Satisfactionmentioning
confidence: 99%
“…It showed that female teachers hold negative perceptions about their pay, supervision and promotion, thus producing a low level of overall job satisfaction, while their male counterparts hold favorable opinions about pay, promotion policies and supervision and thus indicating high level of job satisfaction. The analysis on gender differences in job satisfaction among full time workers in various fields by Hodson (1989) revealed that there are a number of differences between men and women in determining job satisfaction based on factors such as job characteristics, family responsibilities and personal expectations. Similarly, a study by Carleton and Clain (2012) suggest that there is greater job satisfaction among women but it was limited to married workers.…”
Section: Job Satisfaction and Gender Differencesmentioning
confidence: 99%